Potential of adipose-derived stem cells in muscular regenerative therapies - Forcales, Sonia-V (Frontiers in Aging Neuroscience, 2015)
Regenerative capacity of skeletal muscles resides in satellite cells, a self-renewing population of muscle cells. Several studies are investigating epigenetic mechanisms that control myogenic proliferation and differentiation to find new approaches that could boost regeneration of endogenous myogenic progenitor populations. In recent years, a lot of effort has been applied to purify, expand and manipulate adult stem cells from muscle tissue. However, this population of endogenous myogenic progenitors in adults is limited and their access is difficult and invasive. Therefore, other sources of stem cells with potential to regenerate muscles need to be examined. An excellent candidate could be a population of adult stromal cells within fat characterized by mesenchymal properties, which have been termed adipose-derived stem cells (ASCs). These progenitor adult stem cells have been successfully differentiated in vitro to osteogenic, chondrogenic, neurogenic and myogenic lineages. Autologous adipose-derived stem cells are multipotent and can be harvested with low morbidity; thus, they hold promise for a range of therapeutic applications. This review will discuss the use of ASCs in muscle regenerative approaches.